Prevention and coping in child and family care : mothers in adversity coping with child care - Sheppard, Michael (Jessica Kingsley Publishers, 2004)
How do mothers cope with child care and associated problems when, in adversity, they do not gain access to social service support? This book considers the important question of mothers' coping strategies when they are in adversity. Drawing upon the women's own accounts, it focuses not only on what they do themselves to deal with their problems, but how they integrate their own problem solving approaches with the use of supports. It also examines the way in which women cope with their own emotional responses to these problems. The women themselves, and their own accounts are placed 'centre stag.